At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

8p + 2q = -16
2p - q=2


Sagot :

Answer:

p = -1  q = -4

Step-by-step explanation:

a system of eq and solve for p and q ???  can do  :)

Eq. 1)  8p + 2q = - 16

Eq. 2)  2p - q = 2

use Eq .2 and solve for q

2p - 2 = q

plug into Eq.1 with q

8p +2(2p - 2) = - 16

8p +4p -4 = -16

12p = - 12

p = -1

plug -1 into Eq. 1 for p and solve for q

8(-1) + 2q = - 16

-8 + 2q = - 16

2q = -8

q = -4